The evolution of agricultural research in Africa: Key trends and institutional developments - Roseboom, Johannes; Flaherty, Kathleen (International Food Policy Research Institute, 2016)
This chapter provides an overview of the structure of agricultural research in SSA; its development through time; and its struggle with widespread, systemic constraints. It begins with an overview of the region’s NARSs, followed by a discussion of supranational agricultural research collaboration, before offering an analysis of the constraints affecting the performance of agricultural research in SSA, including (1) policies related to agriculture and agricultural research and development (R&D); (2) the organization and management of agricultural research; (3) human, financial, and physical resources; and (4) collaboration and coordination.